Pancreaticoduodenectomy for an Ampullary Region Carcinoma Occurred in Annular Pancreas Coexistent with Replaced Common Hepatic Artery - Komine, Ryuji (Case Rep Med, 2018)
INTRODUCTION: Annular pancreas is a rare congenital abnormality characterized by a ring of pancreatic tissue surrounding the descending portion of the duodenum. Annular pancreas coexisting with replaced common hepatic artery which is also a rare anatomical variation has not been reported previously. CASE PRESENTATION: A 53-year-old man visited our hospital complaining of epigastric pain. Based on radiological examinations, he was diagnosed as having pancreatitis, annular pancreas, and hepatomesenteric trunk. One month later, obstructive jaundice developed. Endoscopic examination revealed ampullary region carcinoma. We performed pancreaticoduodenectomy using the “artery-first” approach. DISCUSSION: Both annular pancreas and common hepatic artery anomaly are rare. High-quality preoperative imaging and awareness of such rare conditions are necessary for operative safety. Although the embryological relationship between these anomalies is uncertain, the present case may suggest some relevance between the two. CONCLUSION: The “artery-first” approach may be a useful method for pancreaticoduodenectomy in patients who have an anatomical abnormality.